2004
DOI: 10.1007/s10529-004-5134-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of immobilization parameters on growth and lactic acid production by Streptococcus thermophilus and Lactobacillus bulgaricus co-immobilized in calcium alginate gel beads

Abstract: Streptococcus thermophilus and Lactobacillus bulgaricus were co-immobilized in different systems with varying calcium (0.1-1.5 M) and alginate (1-2%, w/v) concentrations. Highest lactic acid production was 35 g l(-1) when both bacteria were in high viscosity beads (1%, w/v alginate) hardened in 0.1 M CaCl2 . The gel bead composition affected size and distribution of entrapped lactic acid bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
1
7
0
2
Order By: Relevance
“…Optimum conditions were defined on the basis of maximum lactic acid production and minimum cell leakage in the fermentation medium. The behaviour of entrapped cells depends on the nature of biological material in beads (Garbayo et al 2004). As reported earlier (Champagne 1994), cell immobilization technology for lactic acid production is well recognized due to high cell masses achieved, good protection from oxygen in growth medium, and few contamination problems.…”
Section: +mentioning
confidence: 91%
See 1 more Smart Citation
“…Optimum conditions were defined on the basis of maximum lactic acid production and minimum cell leakage in the fermentation medium. The behaviour of entrapped cells depends on the nature of biological material in beads (Garbayo et al 2004). As reported earlier (Champagne 1994), cell immobilization technology for lactic acid production is well recognized due to high cell masses achieved, good protection from oxygen in growth medium, and few contamination problems.…”
Section: +mentioning
confidence: 91%
“…The most widely used immobilization method for lactic acid production is gel entrapment (Roy et al 1987, Dong et al 1991, Wang et al 1995, Yoo et al 1996. Entrapment of lactic acid-producing bacteria in gel matrices can protect them from bacteriophages, contaminating bacteria and physico-chemical stresses (Garbayo et al 2004). Many researchers have utilized agricultural wastes like wheat bran, trimming vine shoot etc.…”
Section: Lacticmentioning
confidence: 99%
“…bulgaricus is an important lactobacillus commonly used for fermented milk products (Garbayo et al, 2004;Schiraldi et al, 2006;Li et al, 2009). The metabolic capacities of L. bulgaricus were responsible for the development of milk acidification and formations of texture and aroma (Russell and Diez-Gonzalez, 1998;Siegumfeldt et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Além do efeito protetor da cápsula de alginato para as bactérias probióticas, alguns estudos mostram que a encapsulação de bactérias láticas (BAL) neste material também influencia na produção de ácido lático (ABDEL-RAHMAN et al, 2013). Garbayo et al, (2004) observaram que a produção de ácido lático por Streptococcus thermophilus e Lactobacillus bulgaricus co-encapsulados em alginato de cálcio foi influenciada pela concentração de alginato (1-2% p/v) A encapsulação de BAL bacteriocinogênicas em cápsulas de alginato de cálcio com o objetivo de aumentar a produção de bacteriocina tem sido pouco estudada e parece ser dependente das cepas produtoras de bacteriocina. Scannell et al (2000) observaram que a encapsulação de Lactococcus lactis subsp.…”
Section: Figuraunclassified
“…Some studies have shown that encapsulation of LAB in calcium-alginate improves lactic acid production (Scannell et al, 2000;Garbayo et al, 2004;Idris and Suzana, 2005;Rao et al, 2008), but little is known on bacteriocin production by entrapped LAB. In a previous study, the authors reported that Lactobacillus curvatus…”
Section: Introductionmentioning
confidence: 99%